(3QSGFd CNhGf GdUaG hNdGf GdhaGAs - (3eSdeI Hf CMeO Hf bGSe Hf YHO Gddg GdeLQjWj, CHh GdbGSe,J (B398 (3g` s
(3ChdgG (B:s
(3GdMeOddg GdPi Ndb aShi GYde GjgG GdCN GdHGQ GdQMje CjOc Gddg hCjGfG HQhM efg s
(3BNQgG (B:s
(3GdhGLH Ydjc jG CNj Cf JJbi Gddg ajeG CdbjfGg Edjc ef GdcJH GdeUhfI hGdYdhe GdeMQhSI GdeSJNQLI s
(3HChdg agQSs
(3Hg fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B224 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B234s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B902s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs